Demand analysis of telenursing among empty-nest elderly individuals with chronic diseases based on the Kano model - Yuan, Yuan; Tao, Chunhua; Yu, Ping; Wang, Yanwei; Kitayama, Akio; Takashi, En; Yanagihara, Kiyoko; Liang, Jingyan (Frontiers in Public Health, 2022)
Aim: The increase in empty-nest elderly individuals with chronic diseases poses a major challenge to the provision of public health services in China. Telenursing can effectively relieve the pressure of public health services to a certain extent. This study aims to explore the telenursing needs of empty-nest elderly individuals with chronic diseases based on the Kano model to provide references for improving the quality of telenursing. Methods: Participants were randomly sampled from five rural communities and five urban communities in Yangzhou and Nantong, Jiangsu Province, China. A total of 348 empty-nest elderly individuals with chronic diseases were included. The participants received a sociodemographic characteristics questionnaire, and their telenursing needs were surveyed and analysed based on the Kano model. Results: Of the 15 quality attributes evaluated by the participants, 3 telenursing services were categorized as “must-be quality”, 5 were categorized as “one-dimensional quality”, 5 were categorized as “attractive quality”, and 2 were categorized as “indifferent quality”. The proportion of individuals who desired telenursing services ranged from 47.41% to 83.62%, the better values (satisfaction) ranged from 35.29%-83.98%, and the worse values (dissatisfaction) ranged from 10.91% to 63.27%. There were no significant differences in any items of telenursing needs for between participants in Yangzhou and Nantong (all P>0.05), and there were also no significant differences in all items between rural and urban communities (all P>0.05). Conclusion: Based on the Kano model, it was found that empty-nest elderly individuals with chronic diseases had a positive attitude towards telenursing and that they had different levels of need for different telenursing services. These findings provided a theoretical basis for medical decision-makers to formulate medical policies and provided a scientific foundation for nursing managers to improve telenursing services to meet the needs of the empty-nest elderly individuals with chronic diseases.